Komunikasi Internasional sebagai Sarana Penyelesaian Konflik Laut Natuna Utara - Ramadhani, Harits Andrian; Widyana, Niken Retno; Wardani, Retno Trisna (Global and Policy Journal of International Relations, 2022)
ABSTRACTInternational communication is an important component in international relations. This relates to conflict resolution related to two or more countries. Indonesia as one of the countries in the world cannot be separated from territorial dispute conflicts such as the North Natuna Sea territorial dispute. The North Natuna Sea conflict is a conflict related to many countries. As a complex conflict resolution, means of settlement are needed. Indonesia uses international communication as a means of resolving the North Natuna Sea conflict. So this study aims to find out the basis of international communication used by Indonesia and to investigate further about how Indonesia's international communication is implemented as a means of resolving the North Natuna Sea conflict. This study uses qualitative methods and uses the concept of international communication in order to obtain comprehensive research results. Indonesia has taken a number of actions, starting from a peaceful path to a firm stance, President Joko Widodo is clearly seen using an active actor's role to seek ways of peace and of course has a main focus, namely protecting Indonesia's national interests in Natuna. International communication is indeed the first and main way to bridge problems and find a middle point. Of course it is supported by a number of firm actions so as not to be complacent and of course the attitudes of the two countries which are in tension must still respect existing international law. Keywords: International Communication, facilities, North Natuna SeaDOI:https://doi.org/10.33005/jgp.v10i02.3748